Analisis Penggunaan Aviobridge PT Angkasa Pura II Dalam Menunjang Kegiatan Penerbangan Di Bandara Internasional Supadio Pontianak, Kalimantan Barat - Tasya Rizky Adillah Lubis; Anita Nur Masyi’ah (Jurnal Kajian dan Penelitian Umum, 2023)
The apron movement contro (AMC) crew has the task of operating or using a aviobridge for passanger comfort and safety, as aviobridge provides more protection from the heat, raim, jet blast of airplane engine, noise and dust. In other words aviobridge is o important in supporting flight activities that it is hoped that the use of aviobridge will be done well. . The purpose of this study is to learn how aviobridge procedures and what obstacles aviobridge’s operator faced and how the solution might be. This study uses a qualitative method using primary and secondary data. Data collection techniques of observation, interview, and documentation. The time and place of the study began on November 01, 2022 – November 28, 2022, as suggested by the apron movement control unit in The Internasional Airport Supadio Pontianak, West Kalimantan. The analysis techniques used are the reduction of data, the presentation of data, and the drawing of conclusions. The validity test of data on this study employed technical triangulation method and triangulation of data sources. The results of this study have shown that the use of aviobridge follows by the standard operating procedure (SOP) to create safety and occupational health (K3). Studies also found at the time if aviobridge operation include the lack of human resources, the lack of aviobridge facilities, and the problem with aviobridge itself. The solution to this problem is to increase human resources, to add to aviobridge, and to continue to care for aviobridge..